Preserving students' critical thinking, creative thinking and knowledge acquisitions through problem-based learning online (PBLONLINE) physics integrated curricula course - Fauziah Sulaiman (Universiti Malaysia Sabah, 2012)
Problem-based learning (PBL) is a learning approach, designed where students as focus of the learning. Normally, PBL conducted face-to-face. With recent rapid development of technology afford PBL to implement through online (PBL online). This study is done based on two main objectives: (i) to seek whether the previous PBL online strategy can preserve Physics students' critical thinking, (ii) to seek whether the previous PBL online strategy can preserve Physics students' creative thinking, and (ii) to recommend what is the best PBL online practices in order to preserve science physics students' critical and creative thinking. PBL online implemented into twenty five (25) second year students of Physics with Electronics at University Malaysia Sabah for twenty eight (28) weeks, corresponding to two semesters tudy in two different Physics courses( i.e .,Thermodynamics Physics and Statistical Physics).Watson Glaser Critical Thinking Appraisal( 1980) (WGCTA) test used as main instrument to study the level of students' critical thinking skills, whilst the YanPiaw Creative-Critical Thinking Test developed by Chua (YPCCTT)( 2004) was used to identify students' creative thinking style. These instrument were supported by other instruments such as survey questionnaires and students interview on students involved. Findings shows there is significance difference on WGCTA test, where indicates the development on students' critical thinking. As for the YYPCCTT results show increasing development in students' thinking (i.e.,creativity) style before to after the implementation. Moreover, results also show students' critical and creative thinking being preserved nay there is a positive improvement.R ecommendation on best PBL online practice simple mentin sciences courses also proposed.